The mechanical stability of the world’s tallest broadleaf trees - Jackson, Tobias D.; Shenkin, Alexander F.; Majalap, Noreen; Bin Jami, Jamiluddin; Bin Sailim, Azlin; Reynolds, Glen; Coomes, David A.; Chandler, Chris J.; Boyd, Doreen S.; Burt, Andy; Wilkes, Phil; Disney, Mathias; et al. (Biotropica, 2021)
The factors that limit the maximum height of trees, whether ecophysiological or mechanical, are the subject of longstanding debate. Here, we examine the role of mechanical stability in limiting tree height and focus on trees from the tallest tropical forests on Earth, in Sabah, Malaysian Borneo, including the recently discovered tallest tropical tree, a 100.8 m Shorea faguetiana named Menara. We use terrestrial laser scans, in situ strain gauge data and finite element simulations, to map the architecture of tall tropical trees and monitor their response to wind loading. We demonstrate that a tree's risk of breaking due to gravity or self‐weight decreases with tree height and is much more strongly affected by tree architecture than by material properties. In contrast, wind damage risk increases with tree height despite the larger diameters of tall trees, resulting in a U‐shaped curve of mechanical risk with tree height. Our results suggest that the relative rarity of extreme wind speeds in north Borneo may be the reason it is home to the tallest trees in the tropics. in MALAY is available with online material. Abstrak Faktor‐faktor yang mengehadkan ketinggian maksimum pokok, sama ada ekofisiologi atau mekanikal, telah lama menjadi subjek perdebatan. Di sini kami meneliti peranan kestabilan mekanikal dalam mengehadkan ketinggian pokok dan memberi tumpuan kepada pokok dari hutan tropika tertinggi di Bumi, di Sabah, Borneo Malaysia, termasuk pokok tropika tertinggi yang baru ditemui, Shorea faguetiana 100.8m yang bernama Menara. Kami menggunakan imbasan laser daratan, data pengukur regangan in situ dan simulasi unsur terhingga untuk memetakan seni bina pokok tropika yang tinggi dan memantau tindak balas mereka terhadap pemuatan angin. Kami menunjukkan bahawa risiko pokok patah kerana graviti atau berat badan sendiri berkurang dengan ketinggian pokok dan lebih kuat dipengaruhi oleh seni bina pokok daripada sifat material. Sebaliknya, risiko kerosakan angin meningkat dengan ketinggian pokok walaupun diameter pohon tinggi lebih besar, menghasilkan lengkung berbentuk U di graf risiko mekanik dengan ketinggian pokok. Hasil kajian kami menunjukkan bahawa kelajuan angin yang melampau jarang berlaku di Borneo utara mungkin merupakan sebab ia menjadi rumah bagi pokok‐pokok tertinggi di kawasan tropika. We suggest that its low wind speeds are one of the reasons why Sabah (the land beneath the wind) is home to the tallest trees in the tropics. We found that tall trees were more gravitationally stable, but had a higher risk of wind damage, than shorter trees. This means that the larger diameters of tall trees did not compensate for their increased exposure to the strong winds experienced above the canopy.